Relationship between Emotional Distress and Workplace Influence on Depressive Symptoms among Online Motorcycle Taxi Drivers - Merijanti, Lie Tanu; Hairunisa, Nany; Ridwan, Alvin Muhamad; Pusparini, Pusparini; Meiyanti, Meiyanti; Tjahjadi, Muljadi; Isahak, Marzuki bin (Althea Medical Journal, 2024)
Background: The rise of online motorcycle taxi services, driven by the demand for transportation and new technologies, has created a new landscape for drivers. However, despite the benefits, these drivers are not considered employees and are therefore vulnerable to psychosocial risks. This study aimed to investigate the relationship between psychosocial hazards and depressive symptoms among online motorcycle taxi drivers. Methods: A cross-sectional study was conducted, involving 218 online motorcycle taxi drivers in Jakarta, Bogor, Depok, and Tangerang from September to December 2022. The Copenhagen Psychosocial Questionnaire version III was used to assess psychosocial hazards in the workplace and the likelihood of developing depressive symptoms. A multiple linear regression test was used, with a significance level set of p < 0.05.Results: Most respondents were male, and many had worked for over five years, with the majority working more than 8 hours a day. Emotional burden and workplace influences were positively correlated with depressive symptoms (p = 0.017; β = 0.154; and p = 0.002; β = 0.166, respectively). In contrast, the meaning of work and clarity of roles were negatively correlated with depressive symptoms (p = 0.009; β = -0.161; and p = 0.024; β = -0.195, respectively).Conclusion: This study highlights that emotional stress and workplace influence can exacerbate depressive symptoms, while a clear and meaningful work environment have a positive impact. Healthy lifestyle habits are one of the stress management solutions to improve emotional wellness.